Rancang Bangun Sistem Informasi Bengkel Vespa di Denpasar - Githa, Dwi Putra; Sutramiani, Ni Putu (LPPM STMIK STIKOM Indonesia, 2018)
Vespa is a vehicle that has its own charm of its distinctive shape. Vespa has fanatical fans around the world including in Denpasar Bali, either modern vespa or classic vespa. But sometimes riding a vespa (especially a classic vespa) although routine maintenance of the vespa may still be problematic when driving, whether it's a strike in the middle of the journey, broken clutch rope or tire broke while on the way. Information about the vespa workshop is the information that the vespa rider must know. Geographic information system of vespa workshop in Denpasar can be a solution to provide information about the location and route to the vespa workshop in Denpasar. The system is created using the concept of web-mobile, so that each device is capable of using the system with only the web-browser.The result of designing and building geographic information system of Vespa workshop in Denpasar is system consist of user menu and admin menu. Users can view information about the vespa workshop and the route to the vespa workshop. The admin menu is dedicated to managing vespa workshop data in the system.